2021
DOI: 10.3389/fvets.2021.741115
|View full text |Cite
|
Sign up to set email alerts
|

Novel Approach to Assess Cardiac Function Using Systolic Performance and Myocardial Performance Indices From Simultaneous Electrocardiography and Phonocardiography Recordings in Dogs With Various Stages of Myxomatous Mitral Valve Disease

Abstract: Background and Objective: Myxomatous mitral valve disease (MMVD) progression entails changes in the structural and functional properties of the heart affecting cardiac timings and intervals within the cardiac cycle. Conventionally, echocardiography is used to determine the cardiac time intervals (CTIs) including systolic and myocardial performance indices (SPI and MPI) in evaluating cardiac function. Alternatively, these CTIs can also be measured using simultaneous recordings of electrocardiography (ECG) and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…We did not notice a similar study on healthy dogs. However, we previously reported the use of similar CTI parameters in MMVD dogs [37]. This study found that MPI-F1 may not be interchangeably used with the Tei index as it demonstrated a wide disagreement.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…We did not notice a similar study on healthy dogs. However, we previously reported the use of similar CTI parameters in MMVD dogs [37]. This study found that MPI-F1 may not be interchangeably used with the Tei index as it demonstrated a wide disagreement.…”
Section: Discussionmentioning
confidence: 81%
“…Moreover, the available commercial device measuring both ECG and PCG device ([The Eko DUO ECG + Digital Stethoscope; Eko DUO] Eko Devices Inc., California) is designed mainly for humans with proprietary algorithms and software. Recently, we reported the use of the Eko DUO device to determine CTIs and its feasibility in measuring cardiac function in MMVD dogs [37]. Nevertheless, the development of a novel device designed primarily for dogs can be a supportive tool in describing and evaluating cardiac functions, particularly in areas where STE is limited or inaccessible.…”
Section: Introductionmentioning
confidence: 99%
“…However, the rate of change in the PR interval and R-wave amplitude over time improved the diagnostic ability for left cardiac remodeling. Although several studies have evaluated ECGs in dogs with MMVD in recent years [21,22], to the best of our knowledge, this is the first R-wave amplitude, and mean electrical axis.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies chose to combine groups C and D into a group of symptomatic dogs [ 29 ] or B1 and B2 as an asymptomatic group [ 30 , 31 ] for statistical analysis. The results obtained were also analyzed with a division into asymptomatic and symptomatic dogs [ 32 , 33 ], as in this article.…”
Section: Methodsmentioning
confidence: 99%